2019
DOI: 10.3390/agronomy9110677
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Iron Agronomic Biofortification of Brassicaceae Microgreens

Abstract: Insufficient or suboptimal dietary intake of iron (Fe) and zinc (Zn) represent a latent health issue affecting a large proportion of the global population, particularly among young children and women living in poor regions at high risk of malnutrition. Agronomic crop biofortification, which consists of increasing the accumulation of target nutrients in edible plant tissues through fertilization or other eliciting factors, has been proposed as a short-term approach to develop functional staple crops and vegetab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 77 publications
8
48
0
1
Order By: Relevance
“…Out of seventeen anthocyanins identified in the four genotypes only three isomers were predominant in all the genotypes examined: (Table 3). In agreement with previous studies, Moreno et al [233] concluded that broccoli sprouts could be an excellent source of bioactive compounds rich of flavonoids, including acylated anthocyanins, along with glucosinolates, vitamins, and minerals [234][235][236], and that future studies should evaluate the potential of further enhancing the content of bioactive compounds in broccoli sprouts.…”
Section: Broccoli and Cauliflowersupporting
confidence: 83%
“…Out of seventeen anthocyanins identified in the four genotypes only three isomers were predominant in all the genotypes examined: (Table 3). In agreement with previous studies, Moreno et al [233] concluded that broccoli sprouts could be an excellent source of bioactive compounds rich of flavonoids, including acylated anthocyanins, along with glucosinolates, vitamins, and minerals [234][235][236], and that future studies should evaluate the potential of further enhancing the content of bioactive compounds in broccoli sprouts.…”
Section: Broccoli and Cauliflowersupporting
confidence: 83%
“…Plant water content is an important factor in establishing the turgor of plant cells; an adequate presence of water in plant cells ensures optimal metabolism, in terms of (i) the absorption of salts from the outside (soil or substrate), (ii) proper evapotranspiration, (iii) the regulation of the leaf temperature, and iv) the photosynthetic process [ 37 ]. The results obtained in the present work evidenced that the water content of all of the microgreens was quite high, although they were grown in soil instead of the more commonly used hydroponic or soilless technique [ 5 , 11 , 38 ]. The highest percentage of water was measured in daikon microgreens (93.59%), as was predictable due to their fleshy leaves, while in the other analyzed species it was higher than 85%.…”
Section: Discussionmentioning
confidence: 88%
“…However, in the present report, some data differed from other data that have already been published; these discrepancies can be attributed to different cultivation techniques—e.g., greenhouse conditions—and to differences in the used soil. In the present work, the microgreens were cultivated in an organic substrate instead of the frequently used soilless or hydroponic culture [ 38 ]. Moreover, the harvest time (the day of cultivation of the microgreens at harvest) is not reported frequently enough to allow a comparison [ 5 , 6 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High contents of polyphenols, anthocyanins, and other redox-active compounds, i.e., vitamins, glucosinolates, and minerals, have been found [4][5][6][7]. Modulation of the light regime [8] and the composition of the growth solution for microgreens have shown a high potential for biofortification with minerals [9] and secondary metabolites [10].…”
Section: Introductionmentioning
confidence: 99%